Adrenalectomy Improves Blood Pressure and Metabolic Control in Patients With Possible Autonomous Cortisol Secretion: Results of a RCT - Morelli, Valentina; Frigerio, Sofia; Aresta, Carmen; Passeri, Elena; Pugliese, Flavia; Copetti, Massimilano; Barbieri, Anna Maria; Fustinoni, Silvia; Polledri, Elisa; Corbetta, Sabrina; Arosio, Maura; Scillitani, Alfredo; et al. (Frontiers in Endocrinology, 2022)
Objective: The best approach to patients with adrenal incidentalomas (AI) and possible autonomous cortisol secretion (PACS) is debated. The study was aimed to assess the metabolic effect of adrenalectomy in AI patients with PACS in relation to cortisol secretion parameters, peripheral activation and glucocorticoid sensitivity. Design: multicenter randomized study (NCT number: NCT04860180) Methods: sixty-two AI outpatients (40-75 years) with AI >1 cm and cortisol after overnight dexamethasone suppression test (F-1mgDST) between 50 and 138 nmol/L were randomized to adrenalectomy (Arm A) or conservative approach (Arm B). Fifty-five patients completed the 6-month follow-up, 25 in Arm A (17 females, aged 62.5±10.4 years) and 30 patients in Arm B (24 females, 66.1±9.1 years). Plasma adrenocorticotroph hormone (ACTH), 24h-urinary free cortisol, 24h-urinary free cortisone, F-1mgDST, glucose, lipids, glycated haemoglobin (HbA1c) levels, blood pressure (BP), body weight and treatments variations were assessed. The 24h-urinary free cortisol/cortisone ratio (a 11b-hydroxysteroid dehydrogenase type 2 activity marker), BclI and the N363S variants of glucocorticoid receptor (GR) polymorphisms were also evaluated. Results: BP control ameliorated in 68% and 13% subjects in Arm A and Arm B, respectively (p=0.001) and the glycometabolic control ameliorated in 28% and 3.3% subjects in Arm A and Arm B patients, respectively (p=0.02). Arm A subjects showed more rarely the BP and/or glycometabolic control worsening than Arm B patients (12% and 40%, respectively, p=0.03). The surgical approach was independently associated with the BP amelioration (OR 3.0, 95%IC 3.8-108.3, p<0.001) but not with age, F-1mgDST levels, BMI and hypertension and diabetes mellitus presence at baseline. The 24h-urinary free cortisol/cortisone ratio and the presence of sensitizing GR polymorphisms were not associated to the surgical outcome. The ROC curve analysis showed that the BP control amelioration was associated with F-1mgDST (area under the curve, AUC, 0.82±0.09 P=0.012). The F-1mgDST cut-off with the best compromise in predicting the BP amelioration was set at 75 nmol/L (sensitivity 77%, specificity 75%). Conclusions. AI patients with PACS benefit from surgery in terms of BP and glycometabolic control.